(untitled) (Revista de Crítica Literaria Latinoamericana, 2023)
This article investigates the reasons why it is impossible for wild animals in Andean oral histories to establish a marriage alliance with humans. It is an atrocious alliance, despite the fact that those are beings linked to the tutelary deities, and are charged with their energies, which makes them capable of looking like admired lords. Inimitable for that, it is not conceivable that they join with humans to form bloodlines. Humans and wild animals, despite attracting each other, are beings destined to a distant coexistence.